Definitive chemoradiotherapy in elderly patients with esophageal cancer: Safety and outcome. Issue Volume 7:Issues 1(2023) (25th March 2023) - Kiladze, Ivane; Chkhaidze, Lika; Iovashvili, Aleksandre; Natelauri, Eteri; Sokurashvili, Besik; Mariamidze, Elene; Kacheishvili, Nikoloz; Jeremic, Branislav
Abstract: Objective : The efficacy and safety of definitive chemoradiotherapy (dCRT) for elderly patients with unresectable esophageal cancer (EC) are not yet fully understood. We conducted this study to evaluate the outcome and toxicity in elder patients (65 years and over) of unresectable EC treated with dCRT. Methods : From four Georgian cancer centers with a radiation oncology department, we identified 44 elderly patients with EC suitable according to the study criteria. Overall survival (OS) was estimated from the beginning of treatment and toxicity scored using CTCAE 5.0 criteria. Results : The median age of patients was 70.0 years (range 65–83 years), with male predominance (77.3%) and 59% of patients were with Eastern Cooperative Oncology Group (ECOG) performance status 1. Because of significant dysphagia (grade 3–4) nine patients underwent intervention (stenting or gastrostomy) before dCRT. More than two‐thirds of patients were squamous cell histological type (77.3%). Localization of tumors was equally distributed between the middle and lower parts of the esophagus (38.6%) and in 26 patients (59.1%) tumor length was more than 5 cm. The majority of patients had stage III disease (61.4%). Median survival was 16.0 months (95% confidence interval [CI] 0–35.9). OS at 12 and 24 months was 53.7% and 43.6%, respectively. Fifteen patients (34%) were alive from 2.1 to 5.4 years after treatment. A statistically significant difference ( p  = 0.011) in median OS was found between patients who received full (not reached) versus overall survival (OS) was 9.0 months in patients who received nonfull dose of radiotherapy (RT) (95% CI 2.79–15.2). Additional analysis between age subgroups revealed that elder subgroup patients (>75 years) had the highest OS, compared to younger (65–70 years) and intermediate groups (71–75 years) ( p  = 0.001). The most common adverse events were grade 3–4 leukopenia (43.2%), anemia (29.5%), and esophagitis (27.3%). Conclusion : The results of our study support the feasibility and efficacy of dCRT for unresectable EC in carefully selected elderly patients. Survival was correlated to complete dose of RT and therefore accurate selection of patients is crucial for better long‐term survival. Our study showed that chronological age alone does not reflect a patient's ability to tolerate dCRT. Toxicity of dCRT is always a very important issue and patient selection must be very cautious in geriatric patients, although dCRT might benefit highly selected patients. Abstract :